The perception of parents’ educational style and adults psychological adjustment: a comparison between people with and without depressive disturbances - Araújo, Anabela Fernandes (Paidéia (Ribeirão Preto), 2002)
The issue of possible relationships between perceived parental rearing styles, the development of personality characteristics and psychopathological disorders is a topic of great interest, as many of its aspects remain insufficiently known. In this study we've compared two samples - depressed versus non-depressed adult subjects - assessing their memories of parental rearing styles in childhood and adolescence. Although this is an exploratory research, the results obtained indicate a significant relationship between a number of parental attitudes (overprotection, rejection and emotional support) and adult adjustment or disturbance.